Religious Education - Friedrich Schweitzer (St Andrews Encyclopaedia of Theology, 2023)
The article has its focus on Christian religious education and the Christian (theological) understanding of religious education (including the relationship between religious education and moral education), as opposed to a generic (religious studies) understanding of religious education across different religions. At the same time, it includes the awareness of today’s multi-religious contexts and the tasks of inter-religious education. It is based on a theological point of view but it also refers to theology’s multidisciplinary contexts, especially in the fields of general education and the social sciences but also in respect to legal aspects in the relationship between state-sponsored educational institutions like the school and issues of neutrality and commitment. The breakdown of the article follows the distinction between (1) a historical perspective concerning the development of Christian religious education, (2) a systematic perspective concerning theological as well as educational and societal rationales of Christian religious education, its goals and its shape, including the relationship between theology and the philosophy of education, (3) an empirical perspective which is of growing importance in this field both in terms of capturing the reality of religious education as well as in terms of evaluation, and which must be in close conversation with the social sciences and psychology, and (4) a practical perspective which, even if necessarily only briefly, refers to teaching methods as well as other practical tasks.